A Jewish apocalyptic framework of eschatology in the Epistle to the Hebrews protology and eschatology as background - Lee, Jihye (London Bloomsbury T&T Clark, 2023)
"This book presents a comparative study of the Urzeit-Endzeit eschatology in some Jewish apocalyptic literature for a fresh understanding of the Epistle to the Hebrews"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Apocalyptic Literature -- History and criticism; Apocryphal books (Old Testament); Eschatology, Jewish; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Hochschulschrift